BUDDI-MaNGA II: the star-formation histories of bulges and discs of S0s. Issue 4 (30th May 2022) - Johnston, Evelyn J; Häußler, Boris; Jegatheesan, Keerthana; Fraser-McKelvie, Amelia; Coccato, Lodovico; Cortesi, Arianna; Jaffé, Yara; Galaz, Gaspar; Mora, Marcelo; Ordenes-Briceño, Yasna
ABSTRACT: Many processes have been proposed to explain the quenching of star formation in spiral galaxies and their transformation into S0s. These processes affect the bulge and disc in different ways, and so by isolating the bulge and disc spectra, we can look for these characteristic signatures. In this work, we used buddi to cleanly extract the spectra of the bulges and discs of 78 S0 galaxies in the MaNGA Survey. We compared the luminosity and mass weighted stellar populations of the bulges and discs, finding that bulges are generally older and more metal rich than their discs. When considering the mass and environment of each galaxy, we found that the galaxy stellar mass plays a more significant role on the formation of the bulges. Bulges in galaxies with masses $\ge 10^{10}\, {\rm M}_\odot$ built up the majority of their mass rapidly early in their lifetimes, while those in lower mass galaxies formed over more extended time-scales and more recently. No clear difference was found in the formation or quenching processes of the discs as a function of galaxy environment. We conclude that more massive S0 galaxies formed through an inside-out scenario, where the bulge formed first and evolved passively while the disc underwent a more extended period of star formation. In lower mass S0s, the bulges and discs either formed together from the same material, or through an outside-in scenario. Our results therefore imply multiple formation mechanisms for S0 galaxies, the pathway of which is chiefly determined by a galaxy's current stellar mass.